コスモノート・ポリニヤ スイイキ ノ スイオン コウゾウ ト SSM/I ガゾウ カラ ミタ ポリニヤ ノ トクチョウ - 滝沢, 隆俊; タキザワ, タカトシ; 大島, 慶一郎; オオシマ, ケイイチロウ; 牛尾, 収輝; ウシオ, シュウキ; 河村, 俊行; カワムラ, トシユキ; 榎本, 浩之; エノモト, ヒロユキ; Takizawa, Takatoshi; Ohshima, Kay I.; et al. (1997)
P(論文) コスモノート海(60-68°S, 35-65°Eの水域)において, コスモノート・ポリニヤの特徴を明らかにするため, 1987年から1992年の間, JAREの夏観測で得られた水温データの解析を行った。沿岸域には水温-1.5℃以下の冷い水塊が広範囲に存在した。その沖合い北東から北西にかけて, 水温1℃以上の暖かい周極深層水が150m以深に認められた。1987年から1991年のSSM/I画像の解析によると, 持続性のある典型的コスモノート・ポリニヤが1988年に現れた。その他の年は小規模なポリニヤが散発的に出現するのみでポリニヤ活動は弱い年であった。一方, 約66°S, 50-60°Eの沿岸域には例年頻繁に沿岸ポリニヤが現れた。また, コスモノート・ポリニヤから東に向けて, 点在するポリニヤ列がしばしば認められた。このポリニヤ列は, 大気の南極収れん線と海洋の南極発散域に沿って形成されると考えられる。 Water temperature structure in the Cosmonaut Sea between 60-68°S, 35-65°E in 1987-1992 shows that cold water with temperature below -1.5℃ was present in the coastal region. The Circumpolar Deep Water with temperature higher than 1.0℃ was found below about 150m in depth from northeast to northwest of the cold water area. The SSM/I images in 1987-1991 indicate that polynya activity was intensive in 1988,and a typical Cosmonaut Polynya was observed; due to weak activity, small and sporadic Cosmonaut Polynyas formed in 1987,1989,1990 and 1991. A coastal polynya frequently was observed in every year at about 66°S, 50-60°E. A train of polynyas to the east of the Cosmonaut Polynya often appeared. It is considered that the Atmospheric Convergence Line and Antarctic Divergence Region are responsible for polynya activity in the Cosmonaut Sea. departmental bulletin paper